دراسة بيئية وتصنيفية للعوالق النباتية في مياه سد بكسا - ديب جورج (Latakia University Journal -Biological Sciences Series, 2014)
استمرت هذه الدراسة من شهر أذار 2011 حتى شباط 2012 ، تم جمع عينات شهرية من مياه سد بكسا من أربعة مواقع مختلفة عن بعضها ببعض الصفات الفيزيائية والكيميائية. استطعنا في هذه الدراسة تصنيف (132) نوعاً من العوالق النباتية تتبع لأربع شعب وزعت كما يلي: (59) نوعاً تعود لشعبة الطحالب الذهبية Chrysophyta ،40 نوعاً من الطحالب الخضراء Chlorophyta، و(28) نوعاً من الطحالب الزرقاء Cyanophyta ، و(5) أنواع من الأوغلينات Euglenophyta. بينت التحاليل الفيزيائية والكيميائية لمياه السد اختلاف في القيم بين المواقع المدروسة ، فقد تراوح تركيز شوارد النترات بين 17.7 ملغ/ل في الموقع الثالث و0.3 ملغ/ل في الموقع الثاني وكانت أعلى قيمة لشوارد الفوسفات 18.4ملغ/ل وأدناها 0.01 ملغ/ل، كما لوحظ اختلاف هذه القيم في الموقع نفسه باختلاف الفترة الزمنية. ارتبط تنوع وتوزع العوالق النباتية المدروسة بالعوامل البيئية ، حيث لوحظ غزارة الطحالب الزرقاء في مياه الموقع الثالث القريب من مصب الصرف الصحي الذي يمثل البيئة المناسبة لهذه المجموعة من العوالق النباتية. This study was achieved through Mars 2011 until February 2012 the samples collected monthly from Baksa dam from different four location which differenced each other with chemical and physical qualities. We could in these study classified 132 species of phytoplankton distributed as 59 species belong to chrysophyta, 40 species of chlorophyta and 28 species of cyanophyta , 5 species of Euglenophyta. Physical and chemicalanalyzing ofBaksa waters showed the difference of values between studding regions, The concentration of Nitrate ions ranged between 17.7 mg/l at third location and 0.3 mg/l at second location, The highest rate to Phosphate ions was 18.8 mg/l and the less was 0.01mg/l, and it was noticed the difference in these values in the same region with the difference of period of time. The diversity and distribution of studied phytoplankton correlated with the environmental factors. It was noticed The abundance of cyanophytain the water of third location which near to the sewage channels which is suitable environment to these group of phytoplankton.